PERAN KOMUNIKASI PERSUASIF DARING DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK OLEH GURU BIMBINGAN KONSELING PADA MADRASAH TSANAWIYAH NEGERI 2 MEDAN - Rifda Yani (Balai Diklat Keagamaan Medan, 2022)
This scientific paper is entitled the role of persuasive communication by online in creating the students' character by counseling guidance teachers at Madrasah Tsanawiyah Negeri 2 Medan. The purpose of this study is to determine the role of persuasive communication by online in the formation of student character by counseling guidance teachers at Madrasah Tsanawiyah Negeri 2 Medan. The samples as well as the informans of this study are counseling guidance teachers at MTsN 2 Medan, totaling 6 people. The results of his research is the persuasive communication by onlineis are lessable to creat the students' character. The changes that occur around 0-20%. It must be supported by face-to-face persuasive communication. This is because the success of persuasive communication itself is influenced by the factor of the message being conveyed, it must be seen that the body language of the communicator (counseling guidance teachers) who conveys it and the body language of the communicant (students) who receives the message, besides that the tone of voice is unheard because of the persuasive communication by online, i.e. using WA.